Enhancing Maritime Safety and Navigation: Integrating Visual Cues and Astronomical Learning in Transportation Management Education - Chanra Purnama (Dinasti International Journal of Education Management And Social Science, 2024)
This research investigates the integration of visual cues and astronomical learning methodologies into transportation management education to enhance maritime safety and navigation practices. Through qualitative inquiry and descriptive analysis involving professionals trained at the Maritime Institute, perceptions regarding these methodologies' effectiveness and alignment with international standards were explored. Findings revealed a gap between recognition and integration into educational curricula, highlighting the need for greater emphasis on innovative pedagogical approaches. Despite participants' recognition of their significance, limited exposure to these methodologies was reported. However, both visual cues and astronomical learning were perceived to closely align with international standards, suggesting their potential to promote global best practices within the maritime industry. Addressing professional needs, including enhancing operational efficiency and supporting decision-making processes, emerged as crucial considerations for integrating these methodologies. Moving forward, collaborative efforts between educational institutions, industry stakeholders, and regulatory bodies are imperative to establish standardized guidelines and best practices, ensuring the effectiveness of transportation management education in preparing professionals for the challenges of the maritime landscape.